Pemanfaatan POC Kotoran Lembu Melalui Metode Fermentasi EM4 Di Desa Sialang Kecamatan Bangun Purba - Ingrid Ovie Yosephine; Eka Bobby Febrianto; Saroha Manurung; Sri Murti Tarigan; Fadel Muhammad Ramadhan Pardede; Ahmad Habibie Rambe; Disya Dania; Wildani; Arbiansyah; Amanda Zulianty (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
Hamlet 4 Sialang Village, Bangun Purba Subdistrict, Deli Serdang is an area where most of its residents have income in the agricultural sector. But in the implementation of agriculture, this hamlet has not utilized natural products, in this case cow dung, as a basic ingredient for organic fertilizer that is used in its own agriculture or traded. So this community service report aims to enable the people of Thekelan Hamlet to make compost made from cow dung to improve agriculture and the community's economy. The community service method is carried out in three stages; preparation stage, socialization and application stage, and final stage. The preparation stage was carried out by making a composting module. The socialization stage is carried out in community meetings and special socialization, as well as training in making compost from fermentation using EM4 and starbio on cow dung. The final stage consists of making a final report. The expected result is that the community of Dusun 4 Sialang Village is able to make solid compost made from cow dung that can be used in agriculture, as well as commercialized so that it can improve the community's economy.